Błędy pisowniowe w wiadomościach przesyłanych na kartach pocztowych - Dzienisiewicz, Daniel (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
<span dir="ltr" style="left: calc(var(–scale-factor)*74.66px); top: calc(var(–scale-factor)*104.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.984613);" role="presentation">The aim of the article is to <span dir="ltr" style="left: calc(var(–scale-factor)*180.76px); top: calc(var(–scale-factor)*104.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.997653);" role="presentation">characterise the spelling errors observed in Polish postcard <span dir="ltr" style="left: calc(var(–scale-factor)*75.20px); top: calc(var(–scale-factor)*118.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.967927);" role="presentation">messages. The analysis of the source literature shows that so far little attention <span dir="ltr" style="left: calc(var(–scale-factor)*381.05px); top: calc(var(–scale-factor)*118.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.993949);" role="presentation">has been <span dir="ltr" style="left: calc(var(–scale-factor)*75.32px); top: calc(var(–scale-factor)*132.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01782);" role="presentation">paid to <span dir="ltr" style="left: calc(var(–scale-factor)*105.75px); top: calc(var(–scale-factor)*132.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01066);" role="presentation">errors occurring in unsupervised communication. For this reason, nearly 700 <span dir="ltr" style="left: calc(var(–scale-factor)*75.25px); top: calc(var(–scale-factor)*146.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.980977);" role="presentation">errors from around 3,000 texts sent via postcards in the second half of the 20th century <span dir="ltr" style="left: calc(var(–scale-factor)*74.93px); top: calc(var(–scale-factor)*160.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.976933);" role="presentation">were examined. The author discusses individual errors and presents their typology, con<span dir="ltr" style="left: calc(var(–scale-factor)*75.25px); top: calc(var(–scale-factor)*174.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.990198);" role="presentation">cluding that the most common <span dir="ltr" style="left: calc(var(–scale-factor)*197.53px); top: calc(var(–scale-factor)*174.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.985234);" role="presentation">mistakes concern the conventional and historical princi<span dir="ltr" style="left: calc(var(–scale-factor)*75.32px); top: calc(var(–scale-factor)*188.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.964575);" role="presentation">ples of Polish spelling. This conclusion <span dir="ltr" style="left: calc(var(–scale-factor)*228.80px); top: calc(var(–scale-factor)*188.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0175);" role="presentation">to a <span dir="ltr" style="left: calc(var(–scale-factor)*244.74px); top: calc(var(–scale-factor)*188.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.969921);" role="presentation">large extent confirms the results of previous<span dir="ltr" style="left: calc(var(–scale-factor)*75.16px); top: calc(var(–scale-factor)*202.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01679);" role="presentation">research on <span dir="ltr" style="left: calc(var(–scale-factor)*124.21px); top: calc(var(–scale-factor)*202.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.98028);" role="presentation">the spelling practice of Polish speakers and the so-called “difficult words”.